Pengaruh Kompetensi Pegawai terhadap Kualitas Pelayanan Administrasi Terpadu Kecamatan (Paten) di Kecamatan Kuranji Kota Padang - Najmi Rahmadhani (Journal of Education on Social Science (JESS), 2017)
This study was motivated by various problems of dissatisfaction felt by the society to the less qualified service from employees in the public sector. This study aims to determine whether the competence of employees influence the quality of services in the District Integrated Administration Services (PATEN) in Kuranji Subdistrict, Padang City. This is a quantitative study. The population in this study consisted of 96,098 people with the sample of 398 respondents. The sampling technique used in this study was proportional sampling technique. The data of this study were analyzed with simple linear regression analysis. The result of data analysis showed that the competence of employees had a positive and significant influence on the quality of PATENT service in Kuranji Subdistrict, Padang City with total influence of 53.7%. This showed that the higher the competence of the employees would be the higher the quality of service PATENT in the Kuranji Subdistrict.